2013
DOI: 10.1111/jan.12072
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of a nurse telephone follow‐up on paediatric tonsillectomy pain management and complications

Abstract: Nurse telephone follow-up was beneficial for some pain management and prevention of complications, although better analgesic treatments are needed. The intervention was simple, safe, and appreciated by parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 50 publications
3
45
0
1
Order By: Relevance
“…Reports about the effects on pain of posttonsillectomy nursing interventions administered on children and parents are largely inconsistent. Our results are similar with a prior finding that postoperative nursing intervention did not have a significant impact on the administration of analgesics and pain intensity (Paquette et al, ; Zhu et al, ). This is in contrast to the findings of a systematic review (Chorney, Twycross, Mifflin, & Archibald, ), which demonstrated that interventions to improve parent management of postoperative pain at home improved the children's pain outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Reports about the effects on pain of posttonsillectomy nursing interventions administered on children and parents are largely inconsistent. Our results are similar with a prior finding that postoperative nursing intervention did not have a significant impact on the administration of analgesics and pain intensity (Paquette et al, ; Zhu et al, ). This is in contrast to the findings of a systematic review (Chorney, Twycross, Mifflin, & Archibald, ), which demonstrated that interventions to improve parent management of postoperative pain at home improved the children's pain outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Telephone counseling has been used as a follow‐up measure for children at home (Gischler, Mazer, Poley, Tibboel, & Dijk, ; Jones et al., ; Paquette, May, Fiola, Villeneuve, & Lapointe, ; Pfeil et al., ; Rosbe, Jones, Jalisi, & Bray, ; Stewart, Ragg, Sheppard, & Chalkiadis, ; Young, Siden, & Tredwell, ). As an example, for families of children with congenital abnormalities, nurse‐based counseling on a 24‐hr basis created a chance for early intervention (Gischler et al., ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education before the hospital discharge can be organized for pain management for patients and, accordingly, a pain management protocol developed (Courtenay & Carey, 2008;Howard et al, 2014;Shum et al, 2012). Telephone monitoring has been provided after pediatric spinal surgery (Czarnecki, Garwood, & Weisman, 2007), pediatric tonsillectomy (Paquette et al, 2013), and by a nurse in the management of outpatient postoperative surgical pain and complications (Jonas, 2003). All three studies support the use of telephone monitoring for pain management after hospital discharge.…”
Section: Symptomsmentioning
confidence: 99%
“…3,4 Tonsillectomy patients may experience numerous complications during the early postoperative phase. 1,5,6 Many patients experience pain, nausea, vomiting, decreased fluid and food intake, fever, hemorrhage, dizziness, and constipation. 5 It is therefore important to enhance patients' and caregivers' competency to ensure that they engage in their appropriate role during recovery periods.…”
Section: Introductionmentioning
confidence: 99%
“…10 Follow-up intervention in the form of telephone calls from a nurse has been shown to improve pain management and reduce the occurrence of complications. 5 Studies of preoperative education have presented the positive effects of standardized educational programs for both parents and patients of children who are undergoing inpatient elective surgery. Such programs are designed to improve the parents' knowledge, attitudes, and behavior in relation to their children's postoperative pain management.…”
Section: Introductionmentioning
confidence: 99%